A molecular phylogeny of Staphyleaceae: Implications for generic delimitation and classical biogeographic disjunctions in the family. Issue 2 (7th February 2017) - Harris, AJ; Chen, Ping‐Ting; Xu, Xin‐Wei; Zhang, Jian‐Qiang; Yang, Xue; Wen, Jun
Abstract: Staphyleaceae traditionally comprises three genera of temperate and tropical trees and shrubs: Euscaphis Siebold & Zucc., Staphylea L., and Tuprinia Vent. These genera are clearly supported by morphology, but a recent classification based on four chloroplast genes and nuclear ITS treats Staphylea, Euscaphis, and New World Turpinia in Staphylea s.l. and Old World Turpinia in Dalrympelea Roxb. In this study, our objectives were to (1) resolve the phylogenetic relationships within Staphyleaceae using two nuclear and six chloroplast markers, (2) explore morphological synapomorphies that support major clades, and (3) discuss the implications of our results on generic delimitation and biogeography. Our phylogenetic results show five major clades in Staphyleaceae: (1) Old World Turpinia, (2) New World Turpinia, (3) a clade of exclusively Old World Staphylea, (4) an Asian‐North American clade of Staphylea comprising all New World species and the rest of the Old World ones, and (5) Euscaphis . Within the two clades each of Staphylea and Turpinia, morphological features traditionally used for delimiting the genera may exhibit convergence. Among morphological features examined in this study, we found that pollen is not taxonomically informative, features of leaf teeth and epicuticular waxes show limited support for the traditional genera of Staphylea and Tuprinia, respectively, and petal length (i.e., flower size) is significantly smaller in Old World Turpinia compared to New World Turpinia . With respect to biogeography, our results support a rare disjunction between eastern North America and the Himalayas.